Optimal Restoration Strategy Based on Resilience Improvement for Power Transmission Systems Under Extreme Weather Events. Issue 1 (January 2021) - Yu, Z.Y.; Li, Z.P.; Qian, T.; Huang, K.C.; Chen, X.Y.; Tang, W.H.
Abstract: In the past few years, extreme weather events have threatened operations of power systems. The improvement of resilience for power system becomes crucial. This paper proposes an optimal restoration strategy, considering the resilience index of power transmission systems in restoration processes. Firstly, a typhoon is taken as an example to establish an extreme weather event impact model to obtain the failure probability of lines. Then Monte Carlo method is used to generate fault sets. For each restoration time point, the optimal restoration model is used to acquire the maximum recovery loads. The resilience index of system can be obtained by the resilience assessment methodology during restoration. Finally, the proposed strategy is compared with distance-based strategy in IEEE 6-bus system, which demonstrates the superiority of the proposed strategy.